Optimal control applied to an irrigation planning problem: a real case study in Portugal. (2019) - Lopes, Sofia O.; Pereira, Rui M.S.; Pereira, Paulo A.; Caldeira, Amélia C.; Fonte, Victor Francisco
In this paper, a daily plan model to the irrigation of a crop field using optimal control was developed. This daily plan model have in consideration: weather data (temperatures, rainfall, wind speed), the type of crop, the location, humidity in the soil at the initial time, the type of soil and the type of irrigation. The aim is to minimise the water used in the irrigation systems ensuring that the field crop is kept in a good state of preservation. MATLAB was used to develop our mathematical model and obtain its output. Its results were compared with experimental ones obtained from a real farm field of grass in Portugal. This comparison not only allowed us to validate our model, but also allowed us to conclude that, using optimal control considerable savings in water resources, while keeping the crop safe are obtained. Some real test cases were simulated and the comparison between the optimised water to be used by the irrigation system (calculated by software) and the real amount of water used in irrigation site (on-off control system for irrigation) produced water savings above 10%.